1975
DOI: 10.1148/114.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Evaluation of Pleural Opacities

Abstract: Forty-one patients with substantial pleural opacities on chest films were examined by A-mode and B-mode ultrasound. Ultrasonic examination provides an accurate means of differentiating pleural fluid from other conditions which produce such opacities and is superior to the chest films as a means of localizing fluid. With the gain setting used in this series, fluid collections less than 1 cm thick were missed and were probably obscured by reverberation from the ribs. M-mode scanning provides a simple and accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

1976
1976
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(25 citation statements)
references
References 2 publications
0
22
0
3
Order By: Relevance
“…Thoracic US is the ''gold-standard'' method for studying pleural effusions [9]. It is more sensitive than chest radiography or CT in the detection of small amounts of pleural fluid (less then 10 ml) (Fig.…”
Section: Pleural and Extrapleural Diseasesmentioning
confidence: 99%
“…Thoracic US is the ''gold-standard'' method for studying pleural effusions [9]. It is more sensitive than chest radiography or CT in the detection of small amounts of pleural fluid (less then 10 ml) (Fig.…”
Section: Pleural and Extrapleural Diseasesmentioning
confidence: 99%
“…We uscd ultrasound scanning of the pleura to detect effusions as this has been shown to be reliable and sensitive. Doust et al (1975) concluded that ultrasonography provides an accurate means of differentiating pleural fluid from other conditions which produce such opacities and is superior to the chest film as a means of localizing fluid. Gryminski et al (1976) demonstrated the superiority of ultrasonic diagnosis of pleural effusion over radiologic techniques which included PA, lateral decubitus films and fluoroscopy where necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A ultrassonografia torácica é o melhor método de diagnóstico no estudo da efusão pleural (Doust et al, 1975), uma vez que fornece informações confiáveis sobre a presença, volume e característica do fluido pleural (Hecht, 2008;Mattoon e Nyland, 2004;Stowater e Lamb, 1989;Reichle e Wisner, 2000). Este promove uma excelente janela acústica permitindo a visibilização ultrassonográfica das estruturas intratorácicas.…”
Section: Espaço Pleural E Pleuraunclassified